Aesop's fables - Pirotta, Saviour; Johnson, Richard 1953-; Casey, Jane; Aesop (Boston Kingfisher, 2005)
A collection of eight fables, each introduced by Aesop, the freed slave turned master storyteller, who shares the real-life events that inspired each tale.
The cat's bell -- The lion and the mouse -- The wolf and the dog -- The goose that laid the golden eggs -- The fox and the stork -- The tortoise and the hare -- The frogs that wanted a king -- The jay and the peacocks.
Keywords: Aesop's fables -- Adaptations; Fables; Folklore